PENGARUH MODEL PEMBELAJARAN PENEMUAN (DISCOVERY LEARNING) TERHADAP KEMAMPUAN KONEKSI MATEMATIKA SISWA (Studi Eksperimen Terhadap Siswa Kelas VII SMPN 2 Sindangagung Kabupaten Kuningan Pada Pokok Bahasan Segiempat) - Alif Ringga Persada (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2016)
Ability of connection of student mathematics represent one of the standard process in mathematics study. To be optimal of ability of koneksi of student mathematics require to be looked for by solution. One of alternative which can be gone through by is by applying model the Invention study ( Discovery Learning). Intention of this research is to know the respon student to use model the Invention study ( Discovery Learning), knowing ability of connection of student mathematics and to know the influence model the invention study. This research use the quantitative method having the character of experiment. Goals population in this research is entire student SMPN 2 Sindangagung, while its population is entire student of class of VII SMPN 2 Sindangagung. As for becoming sample is class of VII E, amounting to 31 student. Technique of data collecting consisted of by the enquette of assessment of student and tes. Result of research from hypothesis test indicate that the value t count/calculate at variable model the Invention study ( Discovery Learning) is 6,760, value of at t tables is 2,045. Inferential hence that t count > t of is tables of its meaning there are applying influence model the Invention study ( Discovery Learning) to ability of connection of student mathematics. average value of Ability of good connection student mathematics also that is 80,81.Keyword: Discovery Learning, Mathematics Connection